2004
DOI: 10.2478/bf02475565
|View full text |Cite
|
Sign up to set email alerts
|

Runaway of electrons in dense gases and mechanism of generation of high-power subnanosecond beams

Abstract: New understanding of mechanism of the runaway electrons beam generation in gases is presented. It is shown that the Townsend mechanism of the avalanche electron multiplication is valid even for the strong electric fields when the electron ionization friction on gas may be neglected. A non-local criterion for a runaway electron generation is proposed. This criterion results in the universal two-valued dependence of critical voltage U cr on pd for a certain gas (p is a pressure, d is an interelectrode distance).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The ionization rates in the cathode sheath, however, are negligible since it is essentially free of electrons. It has been shown that runaway ionization processes are dominant only in very short gaps and at low pressures even in extremely high electric fields [31,32]. Hence, for conditions considered in this study, the electron-impact transport and reaction coefficients provided by BOLSIG are sufficiently accurate.…”
Section: Theoretical Frameworkmentioning
confidence: 78%
“…The ionization rates in the cathode sheath, however, are negligible since it is essentially free of electrons. It has been shown that runaway ionization processes are dominant only in very short gaps and at low pressures even in extremely high electric fields [31,32]. Hence, for conditions considered in this study, the electron-impact transport and reaction coefficients provided by BOLSIG are sufficiently accurate.…”
Section: Theoretical Frameworkmentioning
confidence: 78%